(untitled) (SCIENCE TIME JOURNAL, 2026)
This study explores the typology of nature imagery as a link between individual existence and collective cultural memory in “The Old Man and the Sea” and “Fields Inherited from My Father”. Drawing on ecocritical perspectives associated with Lawrence Buell and cultural memory theory developed by Maurice Halbwachs and Jan Assmann, the research applies a comparative-typological approach to analyze the symbolic functions of natural landscapes in the two works. The findings indicate that nature imagery in the first text primarily reflects an existential sphere of individual struggle, while in the second it embodies collective memory and generational continuity. The study demonstrates that nature in literature functions as a mediating structure connecting personal experience with broader cultural meanings.